Is Language Production Planning Emergent From Action Planning? A Preliminary Investigation - Koranda, Mark J.; Bulgarelli, Federica; Weiss, Daniel J.; MacDonald, Maryellen C. (Frontiers in Psychology, 2020)
The nature of syntactic planning for language production is generally thought to reflect language-specific processes, but an alternative is that syntactic planning is emergent from general action planning processes. If so, language and nonlinguistic action planning should have identifiable commonalities, consistent with an underlying shared system. Action and language research have had little contact, however, and such comparisons are therefore lacking. Here we address this gap by taking advantage of a striking similarity between two phenomena in language and action production. One is known as syntactic priming—the tendency to re-use a recently-produced sentence structure—and the second is hysteresis—the tendency to reuse a previously executed abstract action plan, such as a limb movement. We examined syntactic priming/hysteresis in parallel language and action tasks intermixed in a single experimental session. Our goals were to establish the feasibility of investigating language and action planning within the same participants and to inform debates on the language-specific vs. domain-general nature of planning systems. In both action and language tasks, target trials afforded two alternative orders of subcomponents in the participant’s response: in the language task, a picture could be described with two different word orders, and in the action task, locations on a touch screen could be touched in two different orders. Prime trials preceding the target trial promoted one of two plans in the respective domain. Manipulations yielded higher rates of primed behavior in both tasks. In an exploratory cross-domain analysis, there was some evidence for stronger priming effects in some combinations of action and language priming conditions than others. These results establish a method for investigating the degree to which language planning is emergent from a domain-general action planning system.